(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Contributo sottoposto a valutazione SOMMARIO: 1. Primi argomenti sulle unioni same-sex - 2. Lo stato dell’arte nazionale ed europeo fino alla pronuncia dei Giudici amministrativi - 3. La sentenza del Consiglio di Stato n. 4899 del 2015. Il fatto - 4. Il sistema regolatorio di riferimento e il riferimento all’ordine naturale - 5. Matrimonio omosex e ufficiale dello stato civile: il rapporto di supremazia gerarchica - 6. “L’infrangibile ostacolo dell’articolo 29 della Costituzione” - 7. Conclusioni e prospettive. Abstract :This article analyses the debate concerning the legal status of same-sex unions, also considering what the Italian State Council has affirmed in relation to the possibility of recognising a same-sax couples (who have got married abroad) in Italy. In this respect, the author investigates the national and European jurisprudence, which has in fact influenced the decision of administrative Courts, including that of the said State Council. The attention is particularly focused on the most interesting passages of the State Council’s judgment, from both the legal point of view and the methodological approach.